2017
DOI: 10.3389/fmicb.2017.00782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rocket (Eruca sativa) Extract on MRSA Growth and Proteome: Metabolic Adjustments in Plant-Based Media

Abstract: The emergence of methicillin-resistant Staphylococcus aureus (MRSA) in food has provoked a great concern about the presence of MRSA in associated foodstuff. Although MRSA is often detected in various retailed meat products, it seems that food handlers are more strongly associated with this type of food contamination. Thus, it can be easily postulated that any food could be contaminated with this pathogen in an industrial environment or in household and cause food poisoning. To this direction, the effect of roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…[71]. It was found that extracts of E. sativa seeds had a remarkable antibacterial action against S. aureus and B. cereus [72]. Eruca seed oil also exerts antibacterial and antifungal effects [73].…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…[71]. It was found that extracts of E. sativa seeds had a remarkable antibacterial action against S. aureus and B. cereus [72]. Eruca seed oil also exerts antibacterial and antifungal effects [73].…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…Interestingly, a study by Doulgeraki et al . [ 46 ] investigated the growth of methicillin-resistant Staphylococcus aureus in a watery rocket salad extract and found an inhibitory effect early in the growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…However, for any compound to be effective in the humid environment of a salad washing factory, high water solubility is a prerequisite. Interestingly, a study by Doulgeraki et al [46] investigated the growth of methicillin-resistant Staphylococcus aureus in a watery rocket salad extract and found an inhibitory effect early in the growth phase.…”
Section: Constituents In the Anti-listerial Rocket Salad Fractionmentioning
confidence: 99%
“…The current antimicrobial activities of the leaves and sprouts extracts may attributed to the presence of bioactive compounds such as erucic acid, Novel Research in Microbiology Journal, 2020 isothiocyanates and (-) vebrenon in these extracts, in agreement with the previous findings of Khoobchandani et al, (2010);Paraschos et al, (2011). Recently, Doulgeraki et al, (2017) study showed that there is a notable effect of E. sativa seeds on the antibacterial potential against S. aureus and B. cereus. In addition, Arribas et al, (2019) demonstrated that the presence tocopherols, oryzanol and β-sitosterol in the rice bran are mainly related to the antimicrobial efficacy of rice.…”
Section: Antimicrobial Potential Of E Sativa Leaves and Sprouts Ethamentioning
confidence: 99%